Psychosocial Study of Depression Amongst Women in Western Region of Nepal - Lamichhane, Khim Bahadur; De, Asis; Chakraborty, PK; Sathian, Brijesh; Subba, Sonu H; Jovanovic, Sabine (Asian Journal of Medical Sciences, 2013)
Background In Nepal, 1 - 2 % of the population suffers from severe mental illness, 5 % from moderate mental problems, while 20 - 30 % of all the patients coming to health institutions have some problems related to mental illness. Aims The aim of the study was to describe the socio-demographic profile and problems of the female patients with depression attending psychiatry OPD of Western Regional Hospital & Manipal Teaching Hospital, Pokhara Settings and Design The study was carried out in the Out Patient Department of Psychiatry at Manipal Teaching Hospital and Western Regional Hospital, Pokhara, from May 2005 to April 2006. Material and Method Cohort data of 50 patients from MTH and 50 patients from WRH were collected. The screening criteria for cases for inclusion in the study were as follows: Female patients with headache, mental tension, feeling of hopelessness and persisted sadness in women with abnormal behavior. The diagnosis and management of all the cases were done by the Psychiatrists and doctors of MTH and WRH. The primary source of data was interview of the patients, their relatives and doctors and observation by the study group Statistical Analysis Data were analyzed using descriptive statistics with SPSS, version 16, statistical analysis program (SPSS, Inc., Chicago, IL). Results 71.51% female patients and 48.29% male patients visited psychiatry OPD at MTH during the study period. Likewise, compare to male patients (47.5%), female patients (52.5%) were higher in WRH during the study period. Most of the women in depression were in productive age group in both the hospitals ; 42% between 21-30 yrs followed by 33% in 31- 40yrs, 16% in 41-50yrs and 4% in 51-60 yrs . 17% women were service holder in different fields, 39% were housewives, 7% in Business, 33% were working in Agriculture / laborer and 4% were in miscellaneous fields. Conclusion Higher caste women suffered more from depression and incidence is more in rural than in urban areas. Due to lack of awareness, most of the mental disorders go unreported. Sociological intervention in needed for the treatment of mental health problems. DOI: http://dx.doi.org/10.3126/ajms.v3i4.7777 Asian Journal of Medical Science Vol.3(4) 2012 pp.39-46